COMMUNITY KNOWLEDGE ABOUT MALARIA TREATMENT, BATEALIT AND MAYONG SUBDISTRICTS, JEPARA REGENCY - Suharjo, Suharjo; Mardiana, Mardiana (Badan Penelitian dan Pengembangan Kesehatan, 2009)
Malaria prevalence in endemic areas could result morbidity as well as mortality because of lack of early warning system of malaria program providers in the field and low community participation. A study was conducted in Batealit and Mayong subdistricts to measure of malaria treatment through interview with 100 the knowledge respondents using structured questionnaires. Data analysis was done to obtain descriptive and narrative data regarding education, main occupation, experience of getting and curing malaria. The study revealed that majority of respondent's highest education in Batealit and Mayong was primary school, with the percentage of 37.0% respectively. Most of respondent's occupation in Batealit and Mayong was fishermen, with the proportion of 41% and 24.0% respectively. The number of respondents of suffering malaria in Batealit was lower compared to Mayong, that was 64.0%. The first effort of respondents to cure malaria was curing themselves by taking medicine from vendors, with the percentages of 26,0% in Batealit and in Mayong. The other respondents went to health centers for getting free medicine, with the proportion of 44,0% in Batualit and in Mayong. It seems that level of education would influence the knowledge of respondents and in turn could increase their health status. Therefore, the study suggests that continued dissemination of information regarding malaria and related measures through several kinds of methods would increase community knowledge of malaria treatment. Key words : Malaria, Knowledge, Treatment